2018
DOI: 10.1002/chem.201801441
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Stability of the Oxidized Hole‐Transporting Materials used in Perovskite Solar Cells

Abstract: The vast majority of the hole transporting materials require the use of chemical doping as an essential step for preparation of efficient perovskite solar cells. An oxidized organic hole-transporting material, obtained during a doping procedure, could potentially be one of the weak links in the device composition. It is not uncommon for the solar cell to heat up under summer sun; therefore, all device components must possess some degree of resistance to repetitive thermal stress. In the current publication, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 31 publications
3
99
0
Order By: Relevance
“…[20] As the glass transition temperature of the spiro-OMeTAD is 125 8C [33] and there is no degradation in pristine (non-additivated) spiro-OMeTAD, it can be conclude that the performance decrease is relatedt ot he evaporation of additives. [34] Finally,a nd as discussed before, Kasparavicius et al [25] also reported that oxidized HEL starts to degradea tt hose values of temperature and part reverts back to the original unoxidized material, and the other partr eacts with TBP. The pinholes at the spiro-OMeTAD layer should then be formed because of the fast evaporation of additives during the thermals tress tests.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…[20] As the glass transition temperature of the spiro-OMeTAD is 125 8C [33] and there is no degradation in pristine (non-additivated) spiro-OMeTAD, it can be conclude that the performance decrease is relatedt ot he evaporation of additives. [34] Finally,a nd as discussed before, Kasparavicius et al [25] also reported that oxidized HEL starts to degradea tt hose values of temperature and part reverts back to the original unoxidized material, and the other partr eacts with TBP. The pinholes at the spiro-OMeTAD layer should then be formed because of the fast evaporation of additives during the thermals tress tests.…”
Section: Resultsmentioning
confidence: 68%
“…Even though TBP presents ab oilingp oint of almost 200 8C, Bailie et al showed that this compound in small quantities can possessa na ppreciable equilibrium partial pressure, which allows it to evaporate at temperatures as low as 85 8Ci n dye-sensitized solar cells. [34] Finally,a nd as discussed before, Kasparavicius et al [25] also reported that oxidized HEL starts to degradea tt hose values of temperature and part reverts back to the original unoxidized material, and the other partr eacts with TBP.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…In addition, the V1160 HTM was tested in a dopant‐free configuration. As dopants are known to chemically interact with the HTMs, it is advisable to search for the compounds that ensure sufficient performance without the use of additives. Interestingly, a device with dopant‐free V1160 showed better performance than that of the corresponding Spiro‐OMeTAD‐based device, resulting in a moderate PCE of 12.6%.…”
Section: Methodsmentioning
confidence: 99%